Systemic and Intravitreal Antagonism of the TNFR1 Signaling Pathway Delays Axotomy-Induced Retinal Ganglion Cell Loss - Lucas-Ruiz, Fernando; Galindo-Romero, Caridad; Salinas-Navarro, Manuel; González-Riquelme, María Josefa; Vidal-Sanz, Manuel; Agudo Barriuso, Marta (Frontiers in Neuroscience, 2019)
Here, we have blocked the signaling pathway of tumor necrosis factor α (TNFα) in a mouse model of traumatic neuropathy using a small cell permeable molecule (R7050) that inhibits TNFα/TNF receptor 1 (TNFR1) complex internalization. Adult pigmented mice were subjected to intraorbital optic nerve crush (ONC). Animals received daily intraperitoneal injections of R7050, and/or a single intravitreal administration the day of the surgery. Some animals received a combinatorial treatment with R7050 (systemic or local) and a single intravitreal injection of brain derived neurotrophic factor (BDNF). As controls, untreated animals were used. Retinas were analyzed for RGC survival 5 and 14 days after the lesion i.e., during the quick and slow phase of axotomy-induced RGC death. qPCR analyses were done to verify that Tnfr1 and TNFα were up-regulated after ONC. At 5 days post-lesion, R7050 intravitreal or systemic treatment neuroprotected RGCs as much as BDNF alone. At 14 days, RGC rescue by systemic or intravitreal administration of R7050 was similar. At this time point, intravitreal treatment with BDNF was significantly better than intravitreal R7050. Combinatory treatment was not better than BDNF alone, although at both time points, the mean number of surviving RGCs was higher. In conclusion, antagonism of the extrinsic pathway of apoptosis rescues axotomized RGCs as it does the activation of survival pathways by BDNF. However, manipulation of both pathways at the same time, does not improve RGC survival.